2020
DOI: 10.4025/actascianimsci.v42i1.48425
|View full text |Cite
|
Sign up to set email alerts
|

Auto-lysed yeast and yeast extract effects on dry matter intake, blood cells counts, IgG titer and gene expression of IL-2 in lactating dairy cows under heat stress

Abstract: The objective of this study was to assess the effects of auto-lysed yeast and yeast extract on performance and immune responses of cows in hot climate in the early lactation period. Twenty five lactating dairy cows randomly assigned to 5 groups and 5 replicates. Cows received basal diet with or without auto-lysed yeast (20 or 40 g/d/head) or yeast extract (20 or 40 g/d/head) as on top-dressed. There were no differences for daily dry matter intake, milk production milk fat and the counts of red blood cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, neutrophils and monocytes were increased with HY supplementation. Similarly, Adili et al [ 55 ] reported that neutrophils were increased by the addition of HY to dairy cows. Neutrophils can protect livestock against the most common infectious diseases [ 56 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, neutrophils and monocytes were increased with HY supplementation. Similarly, Adili et al [ 55 ] reported that neutrophils were increased by the addition of HY to dairy cows. Neutrophils can protect livestock against the most common infectious diseases [ 56 ].…”
Section: Discussionmentioning
confidence: 95%
“…This is one of the reasons because a better antioxidant status can lead to a greater production of antibodies [ 28 ]. An increased level of antibodies was detected also in the blood of dairy cows fed with LY or yeast-derived products, with a high content of β-glucans during the transition period, testifying their beneficial role in stressful situations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in fibrolytic, cellulolytic, and lactic acid-utilizing bacteria helped to increase and stabilize the ruminal pH, thus reducing the risk of acidosis and also improving the functionality of the other bacteria, such as the propionate producers [36]. Consequently, the availability of substrates, such as acetate, increased the glucose levels as a result of the maximized digestion of fiber-based feedstuffs [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Moreover, the higher level of propionate, consequent to a better functionality of the other bacteria strains in the rumen, may also play a role in increasing serum glucose concentrations in cattle [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis can be induced by HCl, NaOH, or exogenous proteolytic enzymes, and although efficient, is expensive and generates undesirable subproducts such as NaCl or carcinogenic agents, like monochloropropanol and dichloropropanol. Plasmolysis uses NaCl, toluene or ethanol to accelerate cell lysis, but both soluble and insoluble components, such as dead‐cells, glucans, mannan‐oligosaccharides have to be separated by centrifugation or filtration (Ferreira et al., 2010; Liu et al., 2016; Adili, Sadeghi, Chamani, Shawrang, & Forodi, 2020; Takalloo, Nikkhah, Nemati, Jalilian, & Sajedi, 2020).…”
Section: Metabolic Enzymes and Stress‐enrolled Proteins As Potential ...mentioning
confidence: 99%